2009
DOI: 10.1177/1076029609335518
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Thrombophilia is Associated With Pregnancy Losses That Occur After 12th Gestational Week in Serbian Population

Abstract: Recurrent fetal loss (RFL) is a significant clinical problem, occurring in 1% to 5% of reproductive females. Inherited or acquired thrombophilia has been diagnosed in 50% to 65% of women with history of unexplained fetal loss. The objective of our study was to determine the prevalence of thrombophilia in women with unexplained RFL in Serbian population and to find out whether the presence of thrombophilia is associated with pregnancy losses that occur later than 12th gestational week. We have examined 147 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
3
16
0
2
Order By: Relevance
“…However, the MTHFR 677TT genotype is identified as a high genetic risk factor for recurrent SA, together with the homozygous 5G/5G polymorphism of the PAI-1gene in a Turkish population (Yenicesu et al, 2009). In agreement with this and also with the present study's findings, the homozygous MTHFR 677TT genotype was found with an increased frequency in recurrent SA patients in a Serbian population (Mitic et al, 2010).…”
Section: Disscussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the MTHFR 677TT genotype is identified as a high genetic risk factor for recurrent SA, together with the homozygous 5G/5G polymorphism of the PAI-1gene in a Turkish population (Yenicesu et al, 2009). In agreement with this and also with the present study's findings, the homozygous MTHFR 677TT genotype was found with an increased frequency in recurrent SA patients in a Serbian population (Mitic et al, 2010).…”
Section: Disscussionsupporting
confidence: 91%
“…Numerous studies focus on the mechanism through which hyperhomocysteinemia, hereditary trombophilia (such as protein C or protein S deficiency, the factor V Leiden mutation, the prothrombin G20210A mutation) or combinations of these factors, could influence the normal in utero development and even play a role in spontaneous abortion etiology. Some authors suggest that as many as 60% of pregnancy losses could have been provoked by coagulation disorders (Bick and Hoppensteadt, 2005;Mitic et al, 2010). However, these conclusions are often inconsistent and results are contradictory (Altomare et al, 2007;Robertson et al, 2005;Rodger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In our population, we have also found an increased incidence of thrombophilic abnormalities in women with recurrent pregnancy loss, particularly if these occur after the 12 th gestational week (63,64). Results of the implementation of thromboprophylaxis in these women during subsequent pregnancies are encouraging, particularly for the most frequently found thrombophilias, such as FV Leiden and prothrombin gene mutation G20210A.…”
Section: Pregnancysupporting
confidence: 56%
“…Among five studies (conducted in Israel, 95,100,110 Serbia, 80 and Spain 54 ), a phenotypic test, APCR, was used to determine which women would be tested for the F5 variant. The remaining 37 studies genotyped all women.…”
Section: Case-control Studiesmentioning
confidence: 99%
“…72 Pihusch 89 Many 78 Foka 63 Mitic 80 Souza 98 Sottilotta 97 Kupferminc 112 Hohlagschwandtner 69 Reznikoff-Etievant 92 …”
mentioning
confidence: 99%